Sistem Informasi Kepegawaian Berbasis Web Pada CV. Kilaw Maju Bersama - Darmawan, Muhammad Edo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Resume. Kilaw Forward Together faces issues in employee data management, especially in attendance, permissions, and leave processes that are still done manually and have not been integrated. This condition leads to reduced work efficiency as well as being prone to errors in data recording. This research aims to build a web-based employee information system for improving the effectiveness and efficiency of employee data management. The system development methodology used is the Rational Unified Process (RUP), which consists of four main stages: inception, elaboration, construction, and transition. The implementation of these systems can improve the company’s overall performance through more effective human resource management. Testing showed that the system worked well and could reduce administrative workload as well as speed up data-based decision making. The result of this study was a system capable of managing attendance, leave, and permissions data in real-time as well as providing ease of access for employees, leadership, and administrators.